Effect of compaction treatment on laminated CFRP composites fabricated by vacuum‐assisted resin‐transfer molding. Issue 2 (7th July 2015) - Yoon, Sang‐Jae; Arakawa, Kazuo; Han, Seung‐Wook; Chen, Dingding; Choi, Nak‐Sam
Abstract : Carbon fiber‐reinforced polymer (CFRP) composites were fabricated using ordinary and compaction setups (OS and CS, respectively) in the vacuum‐assisted resin‐transfer molding (VARTM) process. The mechanical properties and acoustic emission (AE) spectra of the CFRP composites were compared among fabricated samples. The CFRP plates with sequences of [+30/−30]6 were sectioned to make specimens for Mode I interlaminar fracture tests and three‐point bending tests. The difference between the material properties and AE characteristics of the OS and CS specimens were statistically compared using one‐way analysis of variance. The OS specimens had a thicker resin layer, a higher resin fraction, larger average fracture toughness, and AE energy corresponding to the Mode I fracture, whereas the CS specimens had more macro‐scale voids and higher bending strength. AE analysis showed that frequency bands in the interlaminar fracture tests corresponding to matrix‐related fracture were dominant for the OS specimens, whereas those corresponding to the mixed fracture mode of the fiber and matrix fracture were dominant for the CS specimens. In the bending tests, mixed fiber‐matrix fractures were dominant for the OS specimens, and fiber‐related fractures were dominant for the CS specimens. In conclusion, the compaction treatment diminished interlaminar fracture toughness, due to the enhanced formation of macro‐scale voids around the fiber bundles during the resin impregnation stage. However, the bending strength improved with an increased fiber volume fraction. POLYM. COMPOS., 38:217–226, 2017. © 2015 Society of Plastics Engineers